2005
DOI: 10.1002/cne.20427
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and molecular tunnels surrounding the forebrain commissures of human fetuses

Abstract: Glial cells and extracellular matrix (ECM) molecules surround developing fiber tracts and are implicated in axonal pathfinding. These and other molecules are produced by these strategically located glial cells and have been shown to influence axonal growth across the midline in rodents. We searched for similar cellular and molecular structures surrounding the telencephalic commissures of fetal human brains. Paraffin-embedded brain sections were immunostained for glial fibrillary acidic protein (GFAP) and vimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 69 publications
1
40
0
Order By: Relevance
“…In humans, immunostaining using GFAP antibody revealed bilateral structures on both sides of the corpus callosum corresponding to the GW and the IGG (Fig. 3), which confirms the findings of Lent et al (2005), who also identified the presence of these structures in the human embryonic brain, and those of Rezaie et al (2003), who analyzed GFAP staining in human fetuses between 19 and 23 weeks. In addition, Northern blot analysis demonstrates that both Slit2, which is secreted by the GW and IGG, and its axonal receptor Robo1 are expressed in the fetal brain at 17 gestational weeks (Fig.…”
Section: Presence Of Midline Structures and Expression Of Guidance Mosupporting
confidence: 80%
See 1 more Smart Citation
“…In humans, immunostaining using GFAP antibody revealed bilateral structures on both sides of the corpus callosum corresponding to the GW and the IGG (Fig. 3), which confirms the findings of Lent et al (2005), who also identified the presence of these structures in the human embryonic brain, and those of Rezaie et al (2003), who analyzed GFAP staining in human fetuses between 19 and 23 weeks. In addition, Northern blot analysis demonstrates that both Slit2, which is secreted by the GW and IGG, and its axonal receptor Robo1 are expressed in the fetal brain at 17 gestational weeks (Fig.…”
Section: Presence Of Midline Structures and Expression Of Guidance Mosupporting
confidence: 80%
“…Midline glial populations such as the glial wedge (GW) and the indusium griseum glia (IGG) have been shown to play critical roles in callosal development by secreting the chemorepellant molecule Slit2, which prevents callosal fibers from entering the septum, and instead guides them across the midline and into the contralateral hemisphere Shu et al, 2003a). The existence of these glial structures in the human embryonic brain has recently been demonstrated by Lent et al (2005). The subcallosal sling, first identified by Silver et al in 1982, is situated at the corticoseptal border and has also been shown to play a role in callosal formation (Silver and Ogawa, 1983).…”
mentioning
confidence: 99%
“…These contrasting results suggest that Nf2 is likely to be required for the development of the ventral midline environment where the anterior commissure forms. GFAP + glia are found surrounding the developing anterior commissure (Lent et al, 2005;Pires-Neto et al, 1998;Silver et al, 1993), although their origin and function have not been established. Future studies are required to determine whether Nf2-Yap signaling regulates the development of these putative anterior commissure guidepost cells and those involved in the formation of other axon tracts (Chedotal and Richards, 2010).…”
Section: Nf2 and Yap Regulate The Development Of Midline Guidepostsmentioning
confidence: 99%
“…1) (Griffiths et al, 2009) and at 13th gestational week both the anterior commissure and optic chiasm are well developed (Ren et al, 2006). The progression of these fibers is facilitated by commissural cellular glial tunnels that provide axonal guidance cues for them along their path (Katz et al, 1983;Lent et al, 2005). During these processes the anterior commissure is surrounded by a glial fibrillary acidic protein + / vimentin + glial tunnel and a tunnel of GFAP-and VN-positive glial cells with TN between the cell bodies from 12 th week post conceptional age until at least 17 th week postovulation (Lent et al, 2005).…”
Section: Embryology Of the Anterior Commissurementioning
confidence: 99%
“…By weeks 10-11(13 weeks post-last menstrual period) some of the fornical fibers cross the midline and form the early hippocampal commissure (Griffiths et al, 2009). Glial fibrillary acidic protein -expressing glial cells were seen surrounding the fornix as of 16-17 weeks postovulation (Lent et al, 2005). The early fornix is a short and slightly curved bundle that contains more hippocampal-septal or septohippocampal fibers that connecting the hippocampus with the septal area (Vasung et al, 2010).…”
Section: Embryology Of the Fornixmentioning
confidence: 99%